2010
DOI: 10.1002/jcb.22515
|View full text |Cite
|
Sign up to set email alerts
|

CDK5 phosphorylates eNOS at Ser‐113 and regulates NO production

Abstract: Phosphorylation of endothelial nitric oxide synthase (eNOS) is key mechanism in response to various forms of cellular stimulation. Through protein nitration by peroxynitrite, eNOS is believed to be responsible for the major abnormalities in several important neurodegenerative diseases including Alzheimer's (AD) and Parkinson's diseases (PD). Recent studies provide important in vivo evidence that hyperactivation of Cdk5 by p25 plays an essential role in the cell death of neurons in experimental models of AD and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Besides serine 1177, other point of phosphorylation may modulate eNOS activity, such as Thr495 and Ser113 22 23 . Thus, we detected the effect of tBHQ on these sites.…”
Section: Resultsmentioning
confidence: 99%
“…Besides serine 1177, other point of phosphorylation may modulate eNOS activity, such as Thr495 and Ser113 22 23 . Thus, we detected the effect of tBHQ on these sites.…”
Section: Resultsmentioning
confidence: 99%
“…3a ). The interaction between nestin and CDK5 modulates downstream molecules, including RAC1 and NOS3 [epithelial nitric oxide synthase (eNOS)] ( 23 25 ). Four of the 5 patients exhibited increased nestin expression and 3 of the 5 patients exhibited decreased CDK5 or RAC1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…In doing so, this work provides the first evidence for an in vivo role of Cdk5 in blood vessel formation. There have been various reports including ours, describing functions of Cdk5 in endothelial cells: in detail, endothelial Cdk5 was implicated in endothelial senescence [ 47 ], in neovascularization after ischemic stroke [ 48 ], and in diseases associated with NO dysfunction [ 49 , 50 ]. Our former studies demonstrated that small molecule Cdk5 inhibitors exert anti-angiogenic effects and that Cdk5 is implicated in endothelial cell migration by regulating the small GTPase Rac1 which was restricted to in vitro assays.…”
Section: Discussionmentioning
confidence: 99%